Identificación a nivel de genomoespecie de aislamientos clínicos del complejo Acinetobacter baumannii-Acinetobacter calcoaceticus, mediante RFLP-PCR de la región intergenica espaciadora de los genes 16s y 23s rRNA (2010)
Different species within the Acinetobacter baumannii-Acinetobacter calcoaceticuscomplex are commonly isolated from the clinical environments. Most of them are multi-resistant and some are the cause of outbreaks, which has led to increased concern in hospitals worldwide. In Colombia, the individual discrimination of species within the complex has not yet been implemented, and phenotypic methods currently used are not sufficient for identification to the species level. Therefore, in this study the 16S-23S rRNA gene intergenic spacer (ITS) was analyzed by RFLP, to identify 140 isolates from four hospitals (identified as A, B, C and D) in Colombia. Of these, 120 isolates (85.7%) belonged to the specie A. baumannii, one (0.71%) belonged to Acinetobacter genospecie 3 and 19 isolates (13.6%) did not belong to any of the four genospecies of the complex and were named during the study as "nameless" isolates. When determining the genetic relationships within the isolates, the ones identified as A. baumannii were highly polyclonal (19 clonal groups) 16 of which were found in hospital C. Hospitals A, B and D shared two clonal groups (II and III) isolated in different years, indicating the significant ability of the bacteria to survive long periods in the hospital environment, increasing opportunities for transmission between patients. This study describes a rapid and easy method for the genospecies level identification of clinical isolates of the Acinetobacter baumannii-Acinetobacter calcoaceticus complex.